Improvement of In Vitro Seed Germination and Micropropagation of Amomum tsao-ko (Zingiberaceae Lindl.) - Quyet V. Khuat; Elena A. Kalashnikova; Rima N. Kirakosyan; Hai T. Nguyen; Ekaterina N. Baranova; Marat R. Khaliluev (Horticulturae, 2022)
Black cardamom (Amomum tsao-ko Crevost & Lemarié) is a spice plant of great commercial value in Vietnam, but with limited propagation ability. Its seeds are characterized by a thick and hard seed coat, a small endosperm, and a small embryo, which are the causes of the physical dormancy of the seeds and low germination. Attempts in this study to improve the germination rate and achieve uniform germination included mechanical scarification, immersion in hot or cold water, acid scarification, and the application of plant growth regulators. Although immersion of seeds in cold water and application of plant growth regulators (PGRs) (gibberellic acid (GA3) and 1-naphtaleneacetic acid (NAA)) showed positive effects on seed germination and subsequent seedling growth, mechanical scarification provided the highest germination rate of black cardamom seeds (68.0%) and significantly shortened germination time (53.7 days) compared to control (16.0% and 74.7 days). On the other hand, an efficient micropropagation protocol has been established using shoot tip explants derived from in-vitro-grown seedlings. Murashige and Skoog (MS) medium supplemented with 4.0 mg/L 6-benzylaminopurine (BAP) + 0.5 mg/L NAA proved to be most suitable for rapid multiplication and rooting, providing a mean of 5.4 shoots per explant, 6.8 cm shoot length, and 16.2 roots per explant after 7 weeks of culture. Well-rooted black cardamom plantlets have been successfully adapted to ex vitro conditions. “Fasco” bio-soil was more suitable for acclimatization, with a 48.9% survival rate, 23.3 cm plant length, and 5.7 leaves per plant after 3 months of planting. Improved germination and multiplication protocols can be used to improve propagation performances and to develop elite of black cardamom planting material.